An Analysis on Rewards and Punishments toward Students’ Motivation in English Learning - Aula Akramah (English LAnguage Study and TEaching, 2021)
Rewards and punishments are one of the strategies used to  motivate students in learning English. This study purpose to find out the kinds of rewards and punishments used by the teacher in motivating students and to know the students’ responses of rewards and punishments in learning English at VIII-I grade at  SMP Islam Ibnu Khaldun. The method used in this study was descriptive study. The participants of this study were an English teacher and 30 students of VIII-I grade. This study used interviews and questionnaires of instruments. Analyzing the data for the interview, the writer included the audio-tape recording, then the writer transcripted what the interviewers said and the writer classified the answers based on the transcription, and then draw the conclusion. To analyze the data the writer used percentage formula of questionnaire. From the results of the interview several rewards were used by the teacher in the classroom; praise, gifts, and grades and there were some punishments that were used by teachers; memorizing vocabulary, writing sentences, reading Al-Qur’an letters and cleaning class. In addition, the results of the questionnaire showed that most students responded positively to the provision of rewards and punishments by the teacher. In addition, 99 % of the students agreed that they became more active, more responsible, and also motivated. It turns out that those who considered punishment to be effective were 100%. Therefore, it could be concluded that implementation of rewards and punishments in learning process was more effective because it can make students study hard.